2nd place, PREMUS best paper competition: implementing return-to-work interventions for workers with low-back pain – a conceptual framework to identify barriers and facilitators - Fassier, Jean-Baptiste; Durand, Marie-José; Loisel, Patrick (Scandinavian Journal of Work, Environment & Health, 2011)
' ' OBJECTIVES ': 'Workplace-based return-to-work (RTW) interventions (programs) for workers with low-back pain are more effective than usual healthcare. Nevertheless, the implementation of such interventions usually encounters many barriers within healthcare systems, workplaces, and insurance systems. The aims of this study were to first construct a conceptual framework to identify barriers and facilitators before implementing RTW interventions and second validate this conceptual framework empirically. ' ' METHODS ': 'We conducted a literature review to identify barriers and facilitators described in three domains: (i) diffusion of innovations; (ii) implementation of healthcare programs; and (iii) implementation of low-back pain clinical guidelines. A selection process was used to identify core dimensions. To validate this framework, we conducted a multiple case study with embedded levels of analysis in two regions of France. Data were collected through semi-structured interviews and focus groups with key participants. ' ' RESULTS ': 'An initial framework was constructed with eight dimensions to be studied before implementation. This framework was eclectic, with different theoretical backgrounds. After the validation phase, some dimensions were modified, resulting in a revised conceptual framework that was theoretically and empirically grounded. ' ' CONCLUSIONS ': 'This conceptual framework is an important contribution to the field of implementation science. It can be used in various settings to identify barriers and facilitators prior to implementing RTW interventions. In line with recommendations on knowledge transfer, this will enable evidence-based implementation strategies to be drawn up, improving intervention uptake and thus facilitating occupational disability prevention in low-back pain.
Keywords: diffusion of innovation; disability; health services research; intervention; low-back pain; program evaluation; return-to-work; sickness absence; vocational rehabilitation